Investigating the effects of Realistic Mathematics Education on mathematical creativity through a mixed-methods approach - Simamora, Rustam Effendy; Ramadhanta, Sury Adellia (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study investigates the effect of Realistic Mathematics Education (RME) on mathematical creativity among 96 seventh-grade students in North Kalimantan. Using an embedded experimental design, students were assigned to an experimental group (RME) and a control group (conventional teaching), each consisting of 32 students. The pretest and posttest showed a significant increase in mathematical creativity in both groups, with a greater increase in the RME group. Interviews indicated that RME positively impacted students' mathematical self-efficacy, proficiency in fractions, and enjoyment of learning. Students also favored teaching on the blackboard and mathematics games, which increased their interest. These findings confirm the effectiveness of RME in enhancing mathematical creativity and suggest further exploration of diverse learning media and icebreakers. This study highlights the potential of RME to foster creativity and recommends its integration into the mathematics curriculum.